Validation of A Story-Based Picture Module for Early Childhood Students: A Study in A Kindergarten in Aceh - Mustika, Rizka Maulida; Anisaturrahmi; Elfiadi; Imami, Muh Khairul Wajedi (Southeast Asia Early Childhood Journal, 2025)
The purpose of this research was to validate a picture-based educational module on animal materials for early childhood students. A quantitative, descriptive research design was used to evaluate the module’s appropriateness based on feedback from experts, teachers, and students. Participants included three experts, six teachers, and eight students, selected through purposive sampling. Descriptive statistical analysis using SPSS—incorporating maximum, minimum, mean, and standard deviation values—was conducted to assess the module’s validity. Results indicated that the module was rated as valid in terms of content, media, and language. Expert validation yielded mean scores of 3.92 for language, 3.61 for media, and 3.72 for content. Teacher evaluations rated the module’s cover and display with means ranging from 3.66 to 4.00, while student feedback on module suitability yielded a range of 3.62 to 4.00. Overall, the module demonstrated validity and suitability for early childhood education, supporting its use in educational settings. The study found that picture-based modules are effective in early childhood education, with high validity across content, media, and language. The collaborative validation process demonstrates their potential for broad applicability in improving engagement and comprehension in a variety of educational environments. The implication of this research indicate that picture-based educational modules are effective tools for engaging young learners, improving comprehension, and improving the quality of educational materials in early childhood education, with the potential for wider application across a variety of subjects and settings.